IDENTIFICATION OF METASOMATIC FAMILIES IN GEOBLOCKS OF UKRAINIAN SHIELD - Sinitsyn, V.; Shunko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper is aimed to refer metasomatites of Ukrainian Shield (USh) to the specific metasomatic families (formations) using the unified system of definitions and terms and to recognize distinctive features of metasomatic rocks for the separate megablocks of the shield. Summarizing the all available data, it can be concluded that restricted list of metasomatic families are identified for the whole of USh. In particular, within USh nearsurface families are not known at all; subvolcanic families are presented in Middle-Dniprean megablock only; but families merely of hypabyssal and abyssal depth levels are shown in other megablocks. Additionally, it has been found that alkaline metasomatic families are evidently prevailing relatively to acid and magnesian-calcian families as well as almost all metasomatic rocks of USh are early or middle Proterozoic. As well it has been found that the separate megablocks of USh are characterized by the specific features of prevalence for different types of metasomatic families. It was concluded that above features of metasomatic rocks distinguish the USh from other Precambrian shields of the world. The authors emphasize that conditionality of hydrothermal-metasomatic processes with general geologic, petrogenetic and tectonic events can give a key knowledge for application of hydrothermaly altered rocks as important petrology and metallogenic indicators.